Law and Rationality: A Historiographical Investigation of the Understanding of Motivation and Human Agency in Early Legal Anthropology - Kaius Tuori (Clio@Themis)
The purpose of this article is to examine how nineteenth-century legal science conceptualized and dealt with otherness in law, with examples of legal phenomena such as ordeal and blood revenge to illustrate how the concept of legal rationality evolved in the early legal anthropology and how it still influences our understanding of legal otherness. It provides new insights on how, in the treatment of specific legal institutions, the ideas of reason and rationality could change as scholars used European medieval history to aid in the understanding of indigenous cultures.